Theoretical and experimental study of disordered Ba0.45Sr0.55TiO3 photoluminescence at room temperature - Souza, I. A.; Gurgel, MFC; Santos, LPS; Goes, M. S.; Cava, S.; Cilense, M.; Rosa, ILV; Paiva-Santos, C. O.; Longo, Elson [UNESP] (Elsevier B.V., 2006)
Disordered and crystalline Ba0.45Sr0.55TiO3 (BST) powder processed at low temperature was synthesized by the polymeric precursor method. The single-phase perovskite structure of the ceramics was identified by the Raman and X-ray diffraction techniques. Photoluminescence at room temperature was observed only in a disordered BST sample. Increasing the calcination time intensified the photoluminescence (PL), which reached its maximum value in the sample heat treated at 300 degrees C for 30 h. This emission may be correlated with the structural disorder. Periodic ab initio quantum-mechanical calculations using the CRYSTAL98 program can yield important information regarding the electronic and structural properties of crystalline and disordered solids. The experimental and theoretical results indicate the presence of intermediary energy levels in the band gap. This is ascribed to the break in symmetry, which is responsible for visible photoluminescence in the material's disordered state at room temperature. (c) 2005 Elsevier B.V. All rights reserved.
Keywords: titanate; photoluminescence; BST; disordered